The Development of the Primary 2 (Grade 2) Students Mathematic Learning Achievements by the Cippa Model - Natnicha Andara and Sutthiporn Boonsong (International Journal of Advanced Science and Technology, 2020)
The purposes of this research were: 1) to develop mathematic learning achievement on division of the primary 2 students by the Cippa Model with an achievement of 70 percent and more, and 2) to compare the mathematic learning achievement on division of primary 2 students by learning management in Cippa Model between before and after learning management.  The samples used were 17 primary 2 students of Ban Mai Thung Din Kor School, in the 2nd semester of the academic year 2019. The research instruments consist of: 1) Mathematic lesson plan, and 2) Achievement test about division for primary 2 students. The statistics used for data analysis were percentage, mean, and standard deviation, and hypothesis testing by using the t-test for non-independent samples. The results of the research revealed that: 1) Mathematic Learning achievement about division had average at 77.33 percent, and 2) Mathematic Learning achievement on division after studying was higher than before learning at the statistical significance level of .05.